Copper-Catalyzed Sonogashira-Type Coupling Reaction of Vinylacetylene ortho-Carborane with Boronic Acid in the Synthesis of Luminophores with Phosphorescent Emission - Timofey D. Moseev; Tair A. Idrisov; Mikhail V. Varaksin; Anton N. Tsmokaluk; Valery N. Charushin; Oleg N. Chupakhin (Reactions)
A synthetic approach to prepare boron-enriched π-conjugated photoactive molecular systems based on ortho-carborane using the Cu(I)-catalyzed Sonogashira-type coupling reaction has been developed. The obtained luminophores have been found to possess absorption in the range of 300 to 400 nm, emission of up to 700 nm, and photoluminescence quantum yields of up to 99% in non-polar solvents. TD-DFT calculations have demonstrated that the luminophores are characterized by phosphorescent emission behavior with a lifetime of about 7 μs. In addition, the rigidochromism for the synthesized compounds has been revealed; particularly, the transition electronic state and bathochromic shift have been elucidated in the emission spectra. The exhibited luminescent characteristics indicate that the elaborated vinylcarborane fluorophores could be considered as promising building blocks in the design of advanced photofunctional materials for molecular electronics.